Technology Readiness and Safety Outcomes in Construction: The Mediating Role of Worker Competence and Moderating Role of Top Management Support - Ishtiaq Ahmad (Journal of ICT, Design, Engineering and Technological Science, 2025)
Construction projects remain highly vulnerable to accidents due to dynamic workflows, hazardous environments, and limitations of conventional safety management approaches. With the growing adoption of Industry 4.0 technologies, construction organizations are in‑creasingly investing in digital safety tools; however, their effectiveness depends on organizational readiness and workforce capability to im‑plement them. Grounded in Socio‑Technical Systems (STS) Theory, this study examines the impact of Technology Readiness (TR) on Safety Climate (SC) and Safety Performance (SP), while assessing the mediating role of Worker Competence (WC)and the moderating influence of Top Management Support (TMS). A quantitative cross‑sectional survey was conducted using responses from 420 construction professionals drawn from both public (n=200) and private (n=220) sector organizations. An engineering‑oriented predictive modeling approach was applied, and the model demonstrated strong predictive performance, explaining 62% of the variance in safety climate (R²=0.62) and 58% in safety perfor‑mance (R²=0.58) with acceptable prediction error (SC: RMSE=0.41, MAE=0.32; SP: RMSE=0.45, MAE=0.35). Scenario analysis indicated that high technology readiness substantially improves predicted SC and SP, while competence improvement and strong management support generate similarly large gains in safety outcomes. Sensitivity analysis identified worker competence as the most influential predictor for both SC and SP,followed by technology readiness and top management support. Further, the sector‑wise comparison revealed that private sector organizations demonstrated a stronger link between technology readiness and increases in worker competence, as well as greater improvements in safety out‑comes associated with readiness, compared to public sector organizations. This suggests that private sector organizations were more effective at converting digital investments into competence and safety gains, possibly due to fewer institutional barriers or different organizational struc‑tures. The study concludes that sustainable safety improvement requires integrated strategies that enhance technology readiness, strengthen workforce competence, and reinforce leadership support to maximize the operational safety value of digital transformation in construction or‑ganizations.